Anesthesia and uncommon diseases - Fleisher, Lee A. (Elsevier Saunders, 2012)
Your awareness of uncommon diseases and possible complications is vital to successful anesthetic patient management. This title offers information on less commonly seen diseases and conditions, including management guidelines. It helps us in understanding of best options and potential difficulties in anesthesia.